Analisis Peran Environmental Attitude pada Hubungan antara Consumer Innovativeness terhadap Purchase Intention - Hany Lubaba; Masyhuri Masyhuri (University of Merdeka Malang, 2022)
This study investigates consumer innovativeness's direct and indirect effects on purchase intention. As a novelty of the study, the researcher added the environmental attitude variable as a mediating variable. This study uses a quantitative approach by using a questionnaire as a research instrument distributed to as many as 160 respondents online. The sampling technique is purposive sampling. Respondents in this study were students from all over Indonesia who met the predetermined criteria. After the data is collected, then do the test for quality using validity and reliability tests. Furthermore, the hypothesis testing uses structural equation modeling with the help of the smartpls program. The results show that consumer innovativeness has a direct effect on purchase intention. Increasing consumer innovativeness can directly increase purchase intention. Furthermore, the environmental attitude variable is proven to mediate the impact of consumer innovativeness on purchase intention. The recommendation for further research is to add moderating variables such as gender and age.